The clinical effect of gratitude extension-construction theory nursing program on bladder cancer patients with fear of cancer recurrence - Qian, Liping; Zhang, Yin; Chen, Hui; Pang, Yuan; Wang, Chenchen; Wang, Liangmei; Zhang, Xiaoqing (Frontiers in Oncology, 2024)
Objective To explore the clinical effect of bladder cancer patients with Fear of Cancer Recurrence (FCR) after applying the gratitude extension construction theory nursing program. Methods 168 patients with bladder cancer hospitalized in the Department of Urology from December 2021 to June 2023 in a hospital are study subjects. The experimental subjects are uniformly designed as an experimental group and a control group, with 52 participants in each group. The former receives routine nursing care, while the later receives nursing interventions based on gratitude extension construction theory. The baseline data, Quality of life Questionnaire-core 30, Quality of Life Questionnaire-non Invasive Bladder Cancer 24, Fear of Progression Questionnaire-Short Form, gratitude level questionnaire, Self-Rating Depression Scale, Self-rating Anxiety Scale, patient compliance behavior score, Overall Survival, and Progression-free Survival are evaluated. Results The basic data revealed no statistical significance. The quality of life questionnaire-core 30 and quality of life questionnaire-noninvasive bladder cancer 24 was no significant difference before treatment and after treatment for 1 month. After 9 months, There was a significant difference in pre-treatment scores. The experimental group had no significant difference before and after treatment. For the overall survival rates, the two groups were 67.25% and 79.56%. The progression-free survival rates were 56.35% and 72.35%, respectively, with statistical difference. The compliance rates were 86.54% and 98.08%. The compliance rate of the experimental group exceeded the control group. After 3, 6, and 12 months, the gratitude level questionnaire score and the fear of progression questionnaire-short form in the experimental group were improved. After 3, 6, and 12 months, the control group had no statistically significant difference in the gratitude level questionnaire and the fear of progression questionnaire-short form scores. Compared with the control group, the scores on the gratitude level questionnaire and the fear of progression questionnaire-short form were significantly higher after 3, 6, and 12 months of intervention. Conclusion After applying the gratitude extension construction theory nursing program, the FCR of bladder cancer patients is